Case Report: Successful management of acute kidney injury following interventional heartworm extraction in a dog with caval syndrome - Jun, Jaehan; Yoon, Jaeyeon; Jung, Joohyun (Frontiers in Veterinary Science, 2025)
A 12-year-old, 7 kg, castrated male, mixed-breed dog presented with lethargy, vomiting, and hemoglobinuria. Heartworm infection was diagnosed through a positive Dirofilaria immitis antigen test, thoracic radiography, and echocardiography, which revealed an extensive worm burden extending into the right atrium, right ventricle, main pulmonary artery, and caudal vena cava, indicative of caval syndrome. Interventional heartworm extraction was successfully performed via jugular venotomy, based on clinical and imaging assessments. However, within 48 h postoperatively, the dog developed acute kidney injury (AKI) characterized by oliguria, pleural effusion, and significantly elevated kidney biomarkers. Despite aggressive medical management, kidney function deteriorated, prompting two sessions of prolonged intermittent renal replacement therapy (PIRRT). After PIRRT, the dog exhibited marked clinical and biochemical improvements. Continuous follow-up demonstrated a progressive recovery of kidney function, which was supported by declining serum creatinine, blood urea nitrogen, and urinary cystatin B levels. Knowingly, this is the first documented report in the veterinary literature describing AKI secondary to caval syndrome following interventional heartworm removal in a dog that was successfully managed with PIRRT. This case underscores the necessity for early identification and management of kidney complications after heartworm extraction and highlights hemodialysis as an effective therapeutic modality for severe AKI associated with caval syndrome.